2016
DOI: 10.1371/journal.pone.0168191
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Diversity of the Critically Endangered Lake Minnow Eupallasella percnurus in Poland and Its Implications for Conservation

Abstract: The lake minnow (Eupallasella percnurus) is critically endangered. In this paper we characterize the genetic properties of this fish over its range of occurrence in Poland and propose the use of this knowledge in its active protection. Twelve populations of lake minnow from across its range in Poland were investigated. 13 microsatellite loci were investigated to evaluate genetic variation and distance among populations. The magnitude of the genetic bottleneck or founder effects was investigated. In the studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…It can be used to identify the best breeding set for either individual or group breeding. This is merely an example of how the software works (although the number of markers should be high enough to track genetic differences both within and between lake minnow populations 16 , 22 ). If any molecular marker is polymorphic and inherited according to Mendelian laws, and numbers can be assigned its their alleles, then it can be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be used to identify the best breeding set for either individual or group breeding. This is merely an example of how the software works (although the number of markers should be high enough to track genetic differences both within and between lake minnow populations 16 , 22 ). If any molecular marker is polymorphic and inherited according to Mendelian laws, and numbers can be assigned its their alleles, then it can be used.…”
Section: Discussionmentioning
confidence: 99%
“…Fin clips were taken, and DNA was extracted from all fin samples using a Genomic Mini AX Tissue SPIN DNA Extraction and Purification Kit (A&A Biotechnology, Poland). The extraction procedure was performed following the manufacturer’s recommendations 16 . The integrity of the DNA samples was visually inspected after their electrophoresis in a 1.5% agarose gel stained with ethidium bromide, and DNA yields were quantified by spectrophotometric analysis 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sikorska and Wolnicki (2011) indicated only one site in the Wielkopolskie voivodeship, and Wolnicki et al (2011c) found two sites in the Kujawsko-Pomorskie voivodeship classified as critically threatened. Generally, at least 75% of habitats of lake minnow are currently in danger of being destroyed (Kaczmarczyk and Wolnicki 2016). In the light of the results, it should be emphasized that the loss of lake minnow habitats is part of a more complex process, which is the loss of the wetland habitats and the resulting decrease in population of most aquatic species.…”
Section: Discussionmentioning
confidence: 99%
“…The global population of lake minnow displays a wide range of morphological variation, which resulted in five distinguished subspecies (Kusznierz et al 2017). Across Poland, however, genetic variation in this species is quite low (Kaczmarczyk and Wolnicki 2016).…”
Section: Study Sitementioning
confidence: 99%